Biogas Filter Based on Local Natural Zeolite Materials - Satriyo Krido Wahono; Wahyu Anggo Rizal (International Journal of Renewable Energy Development, 2014)
UPT BPPTK LIPI has created a biogas filter tool to improve the purity of methane in the biogas. The device shaped cylindrical tube containing absorbent materials which based on local natural zeolite of Indonesia. The absorbent has been activated and modified with other materials. This absorbtion material has multi-adsorption capacity for almost impurities gas of biogas. The biogas  filter increase methane content of biogas for 5-20%. The biogas filter improve the biogas’s performance such as increasing methane contents, increasing heating value, reduction of odors, reduction of corrosion potential, increasing the efficiency and stability of the generator.